Fear of Sexual Harassment and Its Impact on Safety Perceptions in Transit Environments: A Global Perspective - Ceccato, Vania (Violence against women, 2022)
This study reports variation in safety perceptions in transit environments, based on samples of university students in 18 cities on six continents who responded to an identical 45-question survey (N= 13,323 university students). We explore potential links between students’ fears and sexual victimization and conclude that sexual harassment affects their behavior and mobility. Student mobility was affected by avoidance strategies prompting some transit riders to travel at particular times, on travel routes and settings that are deemed especially risky, or even avoiding using transit completely. Findings highlight the importance of city–country contexts for transit safety.